Artesunate: A review of its therapeutic insights in respiratory diseases - Zhang, Jingyuan; Li, Yun; Wan, Jingxuan; Zhang, Mengyuan; Li, Chunxiao; Lin, Jiangtao (Phytomedicine (Stuttgart), 2022)
Artesunate, as a semi-synthetic artemisinin derivative of sesquiterpene lactone, is widely used in clinical antimalarial treatment due to its endoperoxide group. Recent studies have found that artesunate may have multiple pharmacological effects, indicating its significant therapeutic potential in multiple respiratory diseases.BACKGROUNDArtesunate, as a semi-synthetic artemisinin derivative of sesquiterpene lactone, is widely used in clinical antimalarial treatment due to its endoperoxide group. Recent studies have found that artesunate may have multiple pharmacological effects, indicating its significant therapeutic potential in multiple respiratory diseases.This review aims to summarize proven and potential therapeutic effects of artesunate in common respiratory disorders.PURPOSEThis review aims to summarize proven and potential therapeutic effects of artesunate in common respiratory disorders.This review summarizes the pharmacological properties of artesunate and then interprets the function of artesunate in various respiratory diseases in detail, such as bronchial asthma, chronic obstructive pulmonary disease, lung injury, lung cancer, pulmonary fibrosis, coronavirus disease 2019, etc., on different target cells and receptors according to completed and ongoing in silico, in vitro, and in vivo studies (including clinical trials).STUDY DESIGNThis review summarizes the pharmacological properties of artesunate and then interprets the function of artesunate in various respiratory diseases in detail, such as bronchial asthma, chronic obstructive pulmonary disease, lung injury, lung cancer, pulmonary fibrosis, coronavirus disease 2019, etc., on different target cells and receptors according to completed and ongoing in silico, in vitro, and in vivo studies (including clinical trials).Literature was searched in electronic databases, including Pubmed, Web of Science and CNKI with the primary keywords of 'artesunate', 'pharmacology', 'pharmacokinetics', 'respiratory disorders', 'lung', 'pulmonary', and secondary search terms of 'Artemisia annua L.', 'artemisinin', 'asthma', 'chronic obstructive lung disease', 'lung injury', 'lung cancer', 'pulmonary fibrosis', 'COVID-19' and 'virus' in English and Chinese. All experiments were included. Reviews and irrelevant studies to the therapeutic effects of artesunate on respiratory diseases were excluded. Information was sort out according to study design, subject, intervention, and outcome.METHODSLiterature was searched in electronic databases, including Pubmed, Web of Science and CNKI with the primary keywords of 'artesunate', 'pharmacology', 'pharmacokinetics', 'respiratory disorders', 'lung', 'pulmonary', and secondary search terms of 'Artemisia annua L.', 'artemisinin', 'asthma', 'chronic obstructive lung disease', 'lung injury', 'lung cancer', 'pulmonary fibrosis', 'COVID-19' and 'virus' in English and Chinese. All experiments were included. Reviews and irrelevant studies to the therapeutic effects of artesunate on respiratory diseases were excluded. Information was sort out according to study design, subject, intervention, and outcome.Artesunate is promising to treat multiple common respiratory disorders via various mechanisms, such as anti-inflammation, anti-oxidative stress, anti-hyperresponsiveness, anti-proliferation, airway remodeling reverse, induction of cell death, cell cycle arrest, etc. CONCLUSION: Artesunate has great potential to treat various respiratory diseases.RESULTSArtesunate is promising to treat multiple common respiratory disorders via various mechanisms, such as anti-inflammation, anti-oxidative stress, anti-hyperresponsiveness, anti-proliferation, airway remodeling reverse, induction of cell death, cell cycle arrest, etc. CONCLUSION: Artesunate has great potential to treat various respiratory diseases.